دور حوسبة القطاع الصحي الحكومي في الحد من هدر الدواء في مستشفى الأمير حمزة في الأردن - الحموي, فواز; الطويق, عوض (Latakia University Journal - Economic and Legal Sciences Series, 2017)
تهدف هذه الدراسة إلى التعرف على دور حوسبة عمل مستشفى الأمير حمزة في الحد من هدر الدواء والتعرف كذلك على دور هذه الحوسبة في ضبط عمليات وصف وصرف الدواء وإيجاد آلية رقابية لتقليل التكلفة والوقت والجهد .تم استخدام استبانة خاصة للتعرف على أراء عينة الدراسة حول أثر استخدام برنامج الحوسبة في الحد من هدر الدواء مكونة من (15) فقرة وتم التحقق من صدقها وثباتها ووجد أنها مناسبة لغايات البحث العلمي حيث اشتملت عينة الدراسة على (40) طبيبا و (25) صيدلياً. ومن أهم النتائج التي توصلت إليها الدراسة وجود فروق دالة إحصائيا في أراء عينة الدراسة حول أثر الحوسبة في الحد من هدر الدواء تعزى للجنس والوظيفة والمستوى التعليمي، وعدم وجود فروق دالة إحصائيا في أراء عينة الدراسة تعزى للعمر والخبرة .This study aims to identify the role of computerization at the Prince Hamzah Hospital in the reduction of medicine waste and its role in adjusting the operations of prescribing and dispensing medication and to find a mechanism of control to minimize costs, time and efforts.A questionnaire was used to identify the opinions of the study sample on the impact of the use of a computing program in reducing the waste of medication consisting of (15) items whose validity and reliability were validated; the questionnaire was found appropriate for the purposes of scientific research where the sample study consisted of (40) doctors and (25) pharmacists.The most important findings of the study include the presence of statistically significant differences in the opinions of the sample study on the impact of computing on the reduction of the medication wastage due to gender, occupation, and educational level, and the lack of statistically significant differences in the views of the study sample attributed to age and experience.